Development and Pilot of the National Child Traumatic Stress Network Trauma‐Informed Juvenile Court Self‐Assessment. (6th June 2019) - Pickens, Isaiah B.; Howard, Michael L.; Halladay‐Goldman, Jane; Cruise, Keith R.; Watson, Kate R.
Abstract: Trauma‐informed practices in the juvenile justice system are increasingly recognized as effective for promoting public safety through case management, rehabilitation, and treatment that is responsive to a traumatic event exposure and current trauma reactions. As court systems explore integration of trauma‐informed practices, tools for identifying best practices and strategically implementing trauma‐informed approaches are integral for judges and court administrators aiming to develop trauma‐informed courts. The current paper reviews the National Child Traumatic Stress Network's development of the Trauma‐Informed Juvenile Court Self‐Assessment (TI‐JCSA). Implications for self‐guided strategies to shift court practices and policies to align with trauma‐informed approaches will be discussed.